2020
DOI: 10.2147/cia.s259762
|View full text |Cite
|
Sign up to set email alerts
|

<p>Human Adipose Tissue-Derived Mesenchymal Stem Cells in Parkinson’s Disease: Inhibition of T Helper 17 Cell Differentiation and Regulation of Immune Balance Towards a Regulatory T Cell Phenotype</p>

Abstract: Background: Parkinson's disease (PD) is a neurodegenerative disorder displaying a typical neuroinflammation pathology that may result from an imbalance between regulatory T cells (Treg) and T helper 17 (Th17) cells. Human adipose tissue-derived mesenchymal stem cells (Ad-MSCs) exert immunomodulatory effects by inhibiting effector T cell responses and have been used to treat diverse immune disorders. We aimed to investigate the modulating effect of human Ad-MSCs on peripheral blood mononuclear cells (PBMCs) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…In fact, MSC have been reported to influence Th subset differentiation [ 11 ]. For instance, MSC were documented to promote the induction of anti-inflammatory and regulatory Th subsets in vitro [ 41 , 42 , 43 ] while inhibiting pro-inflammatory Th1 cells [ 1 ]. Measurement of Th cytokines in the conditioned media of cocultures allows the detection of a possible shift in the Th1/Th2 subpopulations [ 11 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, MSC have been reported to influence Th subset differentiation [ 11 ]. For instance, MSC were documented to promote the induction of anti-inflammatory and regulatory Th subsets in vitro [ 41 , 42 , 43 ] while inhibiting pro-inflammatory Th1 cells [ 1 ]. Measurement of Th cytokines in the conditioned media of cocultures allows the detection of a possible shift in the Th1/Th2 subpopulations [ 11 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The proposed mechanisms include the secretion of soluble mediators by MSCs, cell-to-cell contact, and the regulation of antigen-presenting cells [ 6 , 42 , 43 ]. In vivo and in vitro studies have shown that MSC therapy increases the number of Tregs in the host [ 44 , 45 , 46 ]. Unfortunately, there is limited evidence on the effect of hAFSCs on Tregs.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulated expression of IL-17A and IL-17F is associated with AS and dual inhibition of these cytokines gives promising results [ 30 ]. Mesenchymal stem cells of various origins are known to support Treg cells and normalize the function of other Th subsets [ 14 , 25 , 31 , 32 ]. However, it is unknown whether AS/ASCs possess such capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Data concerning the effects of MSCs on TGFβ and IL-10 production are inconsistent. Neither MSCs nor MSCs conditioned medium were found to change TGFβ in target cells [ 31 , 55 ], but modulation of this cytokine in T cells was demonstrated [ 49 ]. As for IL-10, unchanged level [ 43 ], increased [ 46 , 47 , 48 , 50 , 55 ], or reduced [ 44 , 49 ] production of this cytokine in MSCs-PBMCs/T cells co-cultures were found.…”
Section: Discussionmentioning
confidence: 99%